2013
DOI: 10.7598/cst2014.669
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Alkaline Pretreatment and Microwave Assisted Enzymatic Hydrolysis of Palm Oil Mill Effluent (POME) for Optimum Fermentable Sugar Yield

Abstract: Abstract:In the present study, a comparison of microwave assisted alkali pretreatment was tried using oil palm empty fruit bunch. The microwave assisted alkali pretreatment of POME using NaOH, significantly improved the enzymatic saccharification of POME by removing more lignin and hemicellulose and increasing its accessibility to hydrolytic enzymes. Enzymatic hydrolysis of POME suspension by various amylolytic enzymes was investigated to reveal the potential coupling mechanism of Microwave Irradiation-Enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…One way to overcome this limitation is to use locally produced enzymes [74]. According to Nomanbhay and Hussain [75], POME is composed of soluble and insoluble carbohydrates. Soluble carbohydrates have a low concentration (0.0039 kg/L), while insoluble carbohydrates have a concentration of 0.026 kg/L in POME.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…One way to overcome this limitation is to use locally produced enzymes [74]. According to Nomanbhay and Hussain [75], POME is composed of soluble and insoluble carbohydrates. Soluble carbohydrates have a low concentration (0.0039 kg/L), while insoluble carbohydrates have a concentration of 0.026 kg/L in POME.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…Using microwave irradiation during pretreatment could also accelerate enzymatic reactions. It has been reported that the enzymatic hydrolysis of POME produced only 0.0238 kg/L of reducing sugar, while microwave-irradiationassisted enzymatic hydrolysis yielded a higher amount of sugar reduction (0.0383 kg/L) [75]. Although the use of lab-scale microwave irradiation pretreatment has significantly improved biogas production, its industrial-scale use is unlikely due to its high cost.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…At 140 W, the temperature of reaction mixture (40-60 o C) was much lower in comparison with temperature at 420 W (80-100 o C). The thermal effect caused the variation in rate of reaction by altering the rate constants of the reaction 13,14 . Thus, it was expected that as the microwave power increased from 140 W to 420 W, reducing sugar concentration would also increase with time.…”
Section: Kinetics Of Single Stage Acid Hydrolysis Facilitated By Micrmentioning
confidence: 99%
“…The dielectric properties of the reaction components determine the performance of a microwave process. Microwave has been successfully used for biomass pretreatment process [11][12][13] . Microwave irradiation accelerates the reaction due to the thermal and non-thermal effects 10,14 .…”
Section: Introductionmentioning
confidence: 99%